2015
DOI: 10.1007/s10853-015-9356-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic coupling in Co-doped ZnS

Abstract: In this paper, we report room-temperature ferromagnetism in chemically synthesized Zn 1-x Co x S (0 B x B 0.10) diluted magnetic semiconductor nanoparticles of *3-5 nm. The incorporation of Co 2? ion for Zn 2? ions in ZnS lattice and the particle size were confirmed by XRD and TEM along with selected area electron diffraction analysis. UV-Vis measurement showed reduction in the bandgap energy with the increase in Co doping. Maximum magnetization was observed for samples with x = 0.04. From photoluminescence, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…They have calculated the partial density of states of 3d-Co and 3p-S as function of energy and shown that in the energy from 0 to −5.0 eV below the Fermi level, d-orbitals of Co and p-orbital of S overlap, indicating the hybridization between S-p and Co-d orbitals. Our result is that a decrease of the band gap energy with increasing the Co dopants is in agreement with [ 29 , 51 ]. Let us emphasize that there are observed results contrary to our result that increases with increasing Fe or Co ion-doping in ZnS NPs [ 18 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…They have calculated the partial density of states of 3d-Co and 3p-S as function of energy and shown that in the energy from 0 to −5.0 eV below the Fermi level, d-orbitals of Co and p-orbital of S overlap, indicating the hybridization between S-p and Co-d orbitals. Our result is that a decrease of the band gap energy with increasing the Co dopants is in agreement with [ 29 , 51 ]. Let us emphasize that there are observed results contrary to our result that increases with increasing Fe or Co ion-doping in ZnS NPs [ 18 ].…”
Section: Resultssupporting
confidence: 92%
“…This is due to the antiferromagnetic super-exchange Co-Co interactions. A maximum ferromagnetic behavior was observed by Patel et al [ 51 ] for 4 % Co-doped ZnS NPs. Let us emphasize that Kumar et al [ 50 ] reported a minimum in the Co concentration dependence of the lattice constant a at x ∼ 0.03 in ZnS NPs, which corresponds to the observed maximum in .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Interesting change in the IR spectra of the samples from S_150 to S_600 can be observed. The peaks observed at $613, $635 and $665 cm À1 in S_150 corresponds to the ZnÀ ÀS vibrations [22]. The intensity of these peaks decreases on increasing the calcination temperature up to 450C as the amount of ZnS is getting decreased in these samples.…”
Section: Ftir Studymentioning
confidence: 92%
“…The band at $1100 cm À1 observed for all the samples itself is due to the CÀ ÀO stretching of the CO 2 adsorbed at the surface of the nanoparticles from the atmosphere. Presence of the water molecule in the samples can also be detected due to the bending mode vibration of HÀ ÀOÀ ÀH observed at $1620 cm À1 [22].…”
Section: Ftir Studymentioning
confidence: 98%